A survey of Alenatea Song et Zhu, 1999 (Aranei: Araneidae) - Marusik YM; Omelko MM; Simonov PS; Mi XQ (KMK SCIENTIFIC PRESS LTD, MOSCOW STATE UNIV, 2022)
Alenatea Song et Zhu, 1999, a genus currently known from three species distributed in the southeastern Palaearctic, is briefly surveyed, and the relationships of the genus are discussed. The previously unknown male of A. wangi Zhu et Song, 1999 is described, and both sexes of A. fuscocolorata (Bosenberg et Strand, 1906) (the generotype) and the female of A. wangi ate redescribed in detail. The possible synonymy of A. touxie Zong et Zhu, 1999 with A. wangi is discussed, and a new combination is proposed as A. acusiseta (Zhu et Song, 1994) comb.n. (ex. Araneus).